Analisis Teologis Narasi Yakobus 4:1-10 Dan Implikasi Bagi Orang Kristen - Masi Rina Laia; Reniati Nabunome (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
God has meaning in creating man. The intended meaning is a life, where life is a strong reason and motivation to support a person in living life according to what he believes. The narrative of James 4:1-10 contains a Biblical pattern of life. However, in today's development, human culture continues to experience changes. The changes in question are behaviors related to morals and ethical values so that humans experience a lot of degradation in the sanctity of their lives. Overcoming this problem, true Christians can have a humble attitude, fear God, fight against sin, rely on God, purify the heart and pray as contained in the narrative of James 4:1-10. This study uses a library research approach. The purpose of this article is to contribute thoughts in the form of alternative solutions to the problems of deviant behavior committed by some Christians today.